Antimicrobial Susceptibility of Campylobacter isolates in the Capital of North Macedonia - Elena Trajkovska-Dokikj; Kiril Mihajlov; Gordana Mirchevska; Marko Kostovski; Aneta Blazevska; Snezana Stojkovska (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2019)
Background: Campylobacter infections are typically self-limited, but in cases with severe enteritis, immu-no-compromised system and bacteremia, an appropriate antimicrobial treatment is demanding. Our study aim was to determine the isolation rate of Campylobacter among patients with acute enteritis in the capital of North Macedonia and its antimicrobial susceptibility. Material and methods: A total number of 3820 patients clinically diagnosed as acute enteritis, were includ-ed in the study. Stool samples were collected and Campylobacter was isolated and identified by classical microbiological methods. Antimicrobial susceptibility of all isolates to Ceftriaxone, Amoxicillin-clavulonic acid, Erythromycin, Ciprofloxacin, Tetracycline and Gentamicin was determined by disc-diffusion technique. Additionally, minimal inhibitory concentrations of all Campylobacter isolates against erythromycin, cipro-floxacin and tetracycline were determined by Epsilon gradient tests.Results: Campylobacter species was isolated in 97 patients. Although the mean isolation rate of Campylobacter spp. during the whole study period was 2.53%, a statistically significant increase was detected in 2016 and 2017, in comparison with the data from previous four years of the study. The isolation rate of Campylobacter spp. didn’t reveal statistically significant difference between males and females (p > 0.05). 46.4 % of patients with Campylobacter enteritis were children at the age under 15 years. Forty-three C. jejuni isolates were susceptible to all six antibiotics, but the remaining 44 isolates revealed resistance to at least one antibiotic. C. coli isolates were resistant to 3 antibiotics simultaneously. Two C. coli isolates only, were susceptible to all 6 antibiotics. 40.90% of C. jejuni and 50% of C. coli isolates were resistant to beta-lactams, fluoroquinolones and tetracyclines, simultaneously. Conclusion: The increase of the isolation rate of Campylobacter from patients with acute enteritis indicates the need for permanent isolation and identification of Campylobacter from every clinically diagnosed patient, as acute enteritis. Erythromicin is the most effective antibiotic for treatment of Campylobacter enteritis in our patients. The high level of Campylobacter resistance to beta-lactams, fluoroquinolones and tetracyclines requires more rational approach in the treatment of Campylobacter enteritis